Analisis Pengaruh Nanofluida TiO2-(Air-Propilen Glikol) Pada Sistem Pendingin Terhadap Kinerja Sistem Pendingin dan Daya Listrik yang Dihasilkan oleh Micropower Generation - M. Ferry Teguh Santoso; Herman Saputro (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
An The use of Micro Power Generation (MPG) or small-scale power plants based on micro combustion using the Thermoelectric Generator (TEG) converter type. This study aims to determine the performance of the TiO2 nanofluid cooling system with the basic fluid of water-propylene glycol mixture on the performance of the cooling system in this case, namely temperature and viscosity, as well as the electric power generated by MPG. The research method used is the experimental method. The variables used are variations in the concentration ratio of the mixture of water with propylene glycol which is used as the base fluid for TiO2 nanofluids in the cooling system. The variation of the ratio used for the mixture of propylene glycol and water is 25%: 75% with a total volume of 2.4 L of cooling fluid and 96 grams of nanoparticles. Tests were carried out by combustion in a double meso vortex combustor with propane gas fuel and air. Then the flame is stabilized with a mass flow meter.  The temperature of the hot side and cold side of the TEG is measured using a thermocouple to produce a temperature difference (∆T) between the two sides. While the resulting output in the form of voltage (Volt) and current (Ampere) is measured with a multimeter and then accumulated in the form of Power (Watt). The results of the study were taken on average produced by nanofluid variations with 25% propylene glycol and 75% water base fluid of 7.08 watts. The average hot side is 148.35 °C, the average cold side is 36.20 °C with the highest voltage of 9.24 V, and an electric current of 0.77 A. This shows that there is an effect of TiO2-(water-propylene glycol) nanofluid in the cooling system on the performance of the cooling system and the electric power generated by the micropower generation.